Strategy for the Effectiveness of the PDI Perjuangan Stelsel CommanderTe in Central Java in the 2024 Election - Dyah Ayu Oktavania; Sri Sutjiatmi; Akhmad Habibullah (Nakhoda: Jurnal Ilmu Pemerintahan)
In the 2024 Legislative Election, the Indonesian Democratic Party of Struggle (PDI-P) implemented the CommanderTe Stelsel strategy in Central Java, which had a significant impact on the acquisition of legislative seats in various districts and cities. This research aims to evaluate the effectiveness of this strategy in mobilizing support and strengthening internal party solidarity. The methods used include outreach, training, and the formation of assisted villages. Analysis was carried out on seat acquisition data from previous election results and after implementing the strategy. The research results show varying impacts in various regions, where some regions experience an increase, decrease, or stability in the number of legislative seats. Challenges faced in implementing this strategy include disputes between legislative candidates and adjusting to changes in voter preferences. However, overall, Commander Te Stelsel's strategy proved effective in mobilizing support and strengthening internal party solidarity. This success shows that this strategy is an interesting innovation in managing competition between legislative candidates. However, this strategy needs to continue to be evaluated and adjusted to ensure its impact is more optimal in the future. Thus, the implementation of this strategy can be a useful model for other political parties in facing election challenges and optimizing their acquisition of legislative seats in the future.